Analisis Faktor-Faktor Yang Mempengaruhi Tingkat Kepatuhan Wajib Pajak Terhadap Kewajiban Perpajakan - Deddy Sulestiyono; Maya Aresteria (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2023)
As the biggest contributor to the state budget, taxes play a very important role in running the wheels of government, and currently 78% of state revenues come from the tax sector. Self-assessment system, is a tax collection system that gives full confidence to taxpayers to calculate, calculate, deposit and report the amount of tax owed on their own. The Self Assessment System requires taxpayers to understand tax laws and regulations in order to understand what their rights and obligations are as taxpayers. Besides that, even this system demands harmonious cooperation between the government as the legislator and the public (taxpayers) as the executor of the law, so that the goals can be achieved. In this study, a sample of 100 MSME actors in Central Java was taken. The type of research used is descriptive qualitative with data collection through questionnaires, observations, and interviews. The method of determining the sample using Purposive Sampling. Data analysis techniques used data reduction, presentation, and conclusion drawing. The results showed that the tax amnesty variable did not have a significant effect on taxpayer compliance, while the tax understanding, tax administration services and tax sanctions variables had a significant effect on tax compliance.